γδ T Cells in Brain Homeostasis and Diseases - Park, Jang Hyun; Kang, In; Lee, Heung Kyu (Frontiers in Immunology, 2022)
γδ T cells are a distinct subset of T cells expressing γδ T cell receptor (TCR) rather than αβTCR. Since their discovery, the critical roles of γδ T cells in multiple physiological systems and diseases have been investigated. γδ T cells are preferentially located at mucosal surfaces, such as the gut, although a small subset of γδ T cells can circulate the blood. Additionally, a subset of γδ T cells reside in the meninges in the central nervous system. Recent findings suggest γδ T cells in the meninges have critical roles in brain function and homeostasis. In addition, several lines of evidence have shown γδ T cells can infiltrate the brain parenchyma and regulate inflammatory responses in multiple diseases, including neurodegenerative diseases. Although the importance of γδ T cells in the brain is well established, their roles are still incompletely understood due to the complexity of their biology. Because γδ T cells rapidly respond to changes in brain status and regulate disease progression, understanding the role of γδ T cells in the brain will provide critical information that is essential for interpreting neuroimmune modulation. In this review, we summarize the complex role of γδ T cells in the brain and discuss future directions for research.